Determinants of Consumptive Behavior in the Context of Islamic Economic Values - Hasallyt, Nena (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Consumptive behavior is a complex phenomenon and is influenced by various factors, both internal and external. This article aims to analyze the determinants of consumer behavior. Using a literature review method, this research identifies four main factors that influence consumer behavior: financial literacy, income, lifestyle and self-control. Financial literacy plays an important role in shaping consumption decisions, where individuals who have a good understanding of financial management tend to make more rational and responsible choices. Income is also the main driver of consumer behavior. Lifestyle, especially in the context of a halal lifestyle, shows how religious norms and values can influence consumption choices, encouraging individuals to shop according to religious teachings. Moreover, self-control plays a crucial role in avoiding excessive consumer behavior, which is often triggered by materialistic desires and social pressure. By integrating Islamic economic principles, such as justice, moderation, and morality, this article proposes that balanced and responsible consumption can be achieved by avoiding wasteful and excessive behavior